Il contributo di Bing Maps per lo studio della città di Ostia Antica (Archeomatica, 2016)
In the last years Bing Maps has been updated to offer new ways for tourism, through the integration of Yelp, Booking, Tripadvisor and Trivago, but it has abandoned the primary aim: a real alternative to Google Earth. Recently a new software suddenly apperead: Esri ArcGis Earth. This will replace definitively Google Earth. After the case study of Veio, Bing Maps returns and shows a hidden "Ostia”, revealing buried structures and building of not excavated areas (Regio III, Regio IV, Regio V and the Harbour of Trajan).